Rezension zu: Unser, Alexander: Social inequality and interreligious learning - Wenig, Eva (Österreichisches Religionspädagogisches Forum, 2020)
Rezension Unser, Alexander: Social inequality and interreligious learning. An empirical analysis of students' agency to cope with interreligious learning tasks, Zürich: LIT Verlag 2019.